Draft genome sequence of Roseovarius sp. PS-C2, isolated from Sekinchan Beach in Selangor, Malaysia - Radzlin, Nurfatini; Mohd Omar, Suhaila; Kian Mau, Goh; Zakaria, Iffah Izzati; Kahar, Ummirul Mukminin (American Society for Microbiology, 2021)
Roseovarius sp. PS-C2 is a bacterium that was isolated from Sekinchan Beach in Selangor, Malaysia, using an ex situ cultivation technique. Here, we present a high-quality annotated draft genome of strain PS-C2 and suggest potential applications of this bacterium.